Amberlyst-15 Catalyzed Synthesis of 12-Aryl-12H-benzo[i][1,3]-dioxolo[4,5-b]xanthene- 6,11-diones and 14-Aryl-14H-dibenzo[a,i]xanthene-8,13-diones under Solvent-Free Condition - Chao, Shujun; Lu, Guangzhou; Wu, Liqiang (Asian Journal of Chemistry, 2011)
Three-component one-pot synthesis of some novel 12-aryl-12H-[1,3]-dioxolo[4,5- b]benzo[i]xanthene-6,11-diones and 14-aryl-14H-dibenzo[a,i]xanthene-8,13-diones, from condensation of 3,4-methylenedioxyphenol or b-naphthol, aldehydes and 2-hydroxy-1,4- naphthoquinone in the presence of Amberlyst-15 under solvent-free conditions at 120 ºC is reported.